Challenges of Iranian national health scientific map - Ahmadreza Izadi; Mohammadkarim Bahadori; Shahram Tofighi; Ali Ebraze; Maryam Yaghoubi; Ehsan Teymourzadeh (Wolters Kluwer Medknow Publications, 2019)
CONTEXT: Iranian National Health Scientific Map is a national plan the implementation of which remarkably influences the progress of the country, though it is facing challenges in its implementation phase. AIMS: The present study has been conducted with the main aim of identifying the challenges facing the comprehensive scientific health map of Iran. SETTING AND DESIGN: This is an applied and qualitative study. SUBJECTS AND METHODS: The study was done in 2017 with the content analysis approach among experts of research and technology management. Some 18 people were selected and were deeply interviewed, meanwhile observing the credibility of research. STATISTICAL ANALYSIS USED: Data analysis was performed based on content analysis and using ATLAS.ti software. RESULTS: Data analysis resulted in the identification of 427 codes, 84 subthemes, and 12 themes. Twelve themes were specified including policy-making, management, university autonomy, quantitative development, consideration of science production chain, designing and monitoring of science map, finance, qualitative assessment, human resources, research ethics, as well as allocating attention to the infrastructure and communication. CONCLUSION: The scientific map of health challenges are indicative of the need for modification of the scientific map and adhering to solutions in line with the removal of the identified challenges. Today, paying attention to the solutions capable of meeting such challenges is a must.